Comparison of Attention Training and Cognitive Therapy in the Treatment of Social Phobia: A Preliminary Investigation. Issue 1 (January 2014) - Donald, Juliet; Abbott, Maree J.; Smith, Evelyn
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Prominent models of social phobia highlight the role played by attentional factors, such as self-focused attention, in the development and maintenance of social phobia. Elevated self-focused attention is associated with increases in self-rated anxiety. Treatments that aim to modify and change attentional processes, specifically self-focused attention, will have a direct effect on social phobia symptoms. Thus, Attention Training targets attentional focus. Aim: The present study aimed to investigate the efficacy of Attention Training in comparison to an established treatment for social phobia, Cognitive Therapy. Method: Participants (Intention-to-treat = 45; completers = 30) were allocated to either 6 weeks of Attention Training or Cognitive Therapy. It was hypothesized that both treatments would be effective in reducing social phobia symptoms, but that Attention Training would work primarily by reducing levels of self-focused attention. Results: The results found an overall effectiveness of both treatment conditions in reducing social phobia symptoms. However, Attention Training significantly improved scores on the Self-Focused Attention questionnaire and the Brief Fear of Negative Evaluation questionnaire compared to Cognitive Therapy. Conclusion: Attention Training seems to be a promising treatment for social phobia.